Penerapan Model Discovery Learning dalam Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar : Studi Literatur - Nur Fadila; Taufina Taufik (Universitas Negeri Padang, 2022)
This research aims to describe the application of the Discovery Learning model in integrated thematic learning in elementary schools. This research is motivated because there are still several problems that occur in the implementation of integrated thematic learning in elementary schools, especially the lack of teacher understanding of the implementation of integrated thematic learning in elementary schools. The method used in this research uses literature study (library research) through literature review to strengthen the analysis of the various sources used. Literature study in this writing is as a basis for forming an initial writing plan and as a secondary data source for writing, secondary data sources in the form of books, online journals, theses, and dissertations as well as other sources relevant to the application of the Discovery Learning model in learning. thematic integrated in elementary schools. The main sources of this research are reputable articles and journals. The results obtained by the writer from the search will be reviewed and analyzed using the content analysis method. Based on the results of the analysis of 15 journals, and reinforced by several theories, it can be concluded that the use of the Discovery Learning model is effective for application and can improve the implementation of integrated thematic learning in elementary schools. It can be seen from the explanation of how the learning planning is designed by the teacher, observations on aspects of the teacher and aspects of students, and the learning outcomes obtained by students.